2018
DOI: 10.1136/neurintsurg-2018-013951
|View full text |Cite
|
Sign up to set email alerts
|

A review of acute ischemic stroke triage protocol evidence: a context for discussion

Abstract: Endovascular thrombectomy (EVT) is now the standard of care for eligible patients with acute ischemic stroke (AIS) secondary to emergent large vessel occlusion (ELVO). However, there remains uncertainty in how hospital systems can most efficiently route patients with suspected ELVO for EVT treatment. Given the relative geographic distribution of centers with and without endovascular capabilities, the value of prehospital triage directly to centers with the ability to provide EVT remains debated. While there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Little evidence is available from clinical studies on triage strategies. 29 The DIRECT-MT trial (Direct Intraarterial Thrombectomy in Order to Revascularize Acute Ischemic Stroke Patients with Large Vessel Occlusion Efficiently in Chinese Tertiary Hospitals: a Multicenter Randomized Clinical Trial) recently showed that EVT alone was noninferior compared with EVT with prior IVT administered within 4.5 hours after symptom onset, which supports the strategy to bypass primary stroke centers when the likelihood of LVO is high. 30 Results from the STRATIS registry (Systematic Evaluation of Patients Treated with Neurothrombectomy Devices for Acute Ischemic Stroke) showed that direct transportation of LVO patients to an intervention center, especially when within 20 miles, may lead to better clinical outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…Little evidence is available from clinical studies on triage strategies. 29 The DIRECT-MT trial (Direct Intraarterial Thrombectomy in Order to Revascularize Acute Ischemic Stroke Patients with Large Vessel Occlusion Efficiently in Chinese Tertiary Hospitals: a Multicenter Randomized Clinical Trial) recently showed that EVT alone was noninferior compared with EVT with prior IVT administered within 4.5 hours after symptom onset, which supports the strategy to bypass primary stroke centers when the likelihood of LVO is high. 30 Results from the STRATIS registry (Systematic Evaluation of Patients Treated with Neurothrombectomy Devices for Acute Ischemic Stroke) showed that direct transportation of LVO patients to an intervention center, especially when within 20 miles, may lead to better clinical outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, an analysis of data from 984 patients enrolled in the Systematic Evaluation of Patients Treated with Stroke Devices for Acute Ischemic Stroke (STRATIS) Registry showed that development of an appropriate triage model with a 20-mile radius for direct to endovascular center care would delay IV tPA administration by only an average of 7 min, but would improve thrombectomy delivery by 94 min 19. This has been demonstrated in multiple other studies, both within and outside the United States 20. Stroke patients would likely be better served if stroke systems aligned more closely with the trauma model, designating regionalized centers of excellence, as was well reviewed in a recent paper in the journal Stroke 21.…”
Section: The Crisis For Stroke Patientsmentioning
confidence: 91%
“…State-wide and county-wide protocols for EMS systems that include a bypass strategy for patients with suspected LVO have been implemented in the United States 15 16. A lot of efforts have also been made to shorten the time interval from symptoms' onset to reperfusion by EVT 17–19…”
Section: Introductionmentioning
confidence: 99%